Flow Injection Determination of Mebeverine Hydrochloride Using Fluorescence Resonance Energy Transfer (Fret) Via Isnag-Fluorimeter - Hayder Q. Munshid (Journal of Global Pharma Technology, 2016)
A new approach was used for the determination of Mebeverine hydrochloride (MIP-HCl) via the fluorescence resonance energy transfer (FRET) from erythrosine B (Erth-B) which used as a carrier stream. The method was applied using flow injection system of a new homemade ISNAG fluorimeter with fluorescence measurements at ± 90◦ via 2×4 solar cell. The linear range for the new developed methodology was 0.01 – 0.6 mmol/L with correlation coefficient r = 0.9577. While the L.O.D was 0.699 µg/sample (sample volume 250 µL) from the stepwise dilution for the minimum concentration in the linear dynamic ranged of the calibration graph. The method was successfully applied to the determination of Mebeverine hydrochloride (MIP-HCl) in three different pharmaceutical drugs. A comparison was made between the newly developed method analysis and the classical method using t-test. It was noticed that there was no significant difference between the two methods at 95 % confidence level.Keywords: Mebeverine hydrochloride, Erythrosine B, Flow injection analysis, Fluorescence Resonance Energy Transfer (FRET).